Practical Synthesis of (9S, 10R)‐9, 10‐epoxy‐(3Z, 6Z)‐henicosadiene: The Major Pheromone of the Saltmarsh Caterpillar moth Estigmene acrea. (17th March 2015) - Kumar, Deepak; Chirumarry, Sridhar; Vijaykumar, B. V. D.; Harshavardhan, S. J.; Jang, Kiwan; Lee, Dong‐Ha; Shin, Dong‐Soo
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10240-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>